Responses of physiological and morphological characteristics in Thai pummelo cultivars (Citrus maxima (Burm.) Merr.) under drought stress condition - Kongsri, Saowanee; Auvuchanon, Anyamanee; Jaroonchon, Nopporn (Agriculture and Natural Resources, 2023)
Importance of the work: Drought is a production problem in Thailand for pummelo and the trees of this fruit have not been evaluated under drought stress. Objectives: To evaluate drought tolerance in nine Thai pummelo cultivars: Thongdee, Khaonamphueng, Khaoyai, Tubtimsiam, Takoy, Khaopan, Khaotaengga, Khaohom and Khaokrun. Materials & Methods: Air-layered pummelo trees (10 plants/cultivar) under drought stress were measured for their physiological and morphological responses (photosynthesis, stomatal conductance and transpiration rate, leaf greenness, relative water content, leaf water potential, proline content, total non-structural carbohydrate (TNC) and plant biomass). All cultivars were grouped based on principal component analysis (PCA). Results: Most parameters in all cultivars decreased after the plants were subjected to drought stress for 12 wk. The plant biomass and TNC decreased, while there were also decreases in the photosynthetic rate, stomatal conductance and transpiration rate to 79.4%, 87.3% and 71.6%, respectively, while leaf greenness decreased by 8.1%. The relative water content decreased by 9.6−37.3%, while the proline content increased 1.4−2.3 times. All cultivars under the control treatment had leaf water potential values from -2.2 to -3.2 MPa and these values decreased to be in the range from -3.5 to -9.0 MPa under drought stress. The measurement results of physiological and morphological parameters and from the PCA were used to classify Khaokrun and Khaotaengga as tolerant pummelo cultivars, and Khaopan, Tubtimsiam and Khaonamphueng as moderately tolerant cultivars, while Takoy, Khaoyai and Thongdee were classified as susceptible cultivars. Main finding: The results could be used to manage pummelo orchards by selecting tolerant cultivars in drought risk areas. Further studies are required to develop drought-tolerant pummelo rootstock.